FACTORS INFLUENCING ON THE QUALITY OF SIMULTANEOUS INTERPRETATION (Ta'limning zamonaviy transformatsiyasi, 2024)
This thesis explores the factors influencing on the quality of simultaneous interpretation, the labyrinthine interplay of elements shaping the effectiveness of simultaneous interpretation, ensuring the highest quality of communication across linguistic barriers.